Assessing and Treating Anxiety in Individuals with Autism. Issue 6 (November 2022) - Moore, Keira; Bullard, Amanda; Sweetman, Gemma; Ahearn, William H.
Anxiety is a cluster of responses that can involve both operant and respondent behavior, which can be both public and/or private in nature, and occurs when an upcoming aversive stimulus is signaled. Despite the reported high comorbidity of autism and anxiety, there has been very limited research on how to directly assess and treat anxiety, especially with individuals who have limited communication skills. In Study 1, anxiety was assessed in five individuals with autism, ranging in age from 10 to 19 years old. Anxiety was assessed by measuring behavior during (1) a baseline (with no putative anxiety-provoking stimuli present), (2) signals for an upcoming aversive event, and (3) exposure to that aversive event. Anxiety presented in several different ways, as both conditioned activation and suppression, and both with and without problem behavior during the aversive event. In Study 2, individualized treatments involving differential reinforcement of alternative responses and stimulus fading were used to successfully reduce anxious responding in all four participants who displayed anxiety. These studies demonstrated a potentially useful means of assessing anxiety in individuals with autism which may not only help to measure anxious behavior and identify anxiety-provoking events, but may also lead to effective treatment.